Analisis Faktor – Faktor yang Mempengaruhi Nilai Cash Holding Pada Perusahaan Sektor Industri Konsumsi yang Terdaftar di BEI - Mhd. Hafiz Maulana; Monica Cheria; Connie Halim; Wilfrida Windra Sari Gea; H.Adam Afiezan (Politeknik Ganesha Medan, 2022)
The consumption industry is a type of business that is developing quite rapidly in Indonesia which results in quite tight competition in the business industry in Indonesia so that it requires business people to be able to run their business and maintain their existence. This study intends to examine the effect of cash flow, growth opportunity, leverage, net profit/loss on cash holding in consumption industry companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The research uses descriptive quantitative methods. The data used is secondary data obtained from the IDX through the https://www.idx.co.id site and obtained a sample of 36 companies that meet the criteria. The data analysis techniques used are: classical assumption test, multiple linear regression and hypothesis testing which includes t test and f test. The conclusion obtained from this study is that cash flow has a positive and significant effect on cash holding, leverage has a negative and significant effect on cash holding, growth opportunity, and net profit/loss has no and no significant effect on cash holding. Based on the coefficient of determination test, it was found that the dependent variable in this study was influenced by all independent variables as much as 34.7% and the remaining 65.3% was influenced by other variables apart from this study